Paternal Involvement in Maternal Healthcare: A Systematic Review of Suami SIAGA in Rural Indonesia - Asyura, Muhammad Mikail Athif Zhafir; Mayhana, Shuffa Chilla; Wijaya, Ilma Ranjani; Naufal, Muhammad Afif (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
Introduction – Maternal health has remained as a nationwide concern especially due to Indonesia’s staggeringly high maternal mortality rate. Community development and promotion on prenatal and antenatal care has been implemented locally especially in rural areas with limited exposure to proper maternal education. Despite that, paternal understanding and involvement in maternal healthcare is a contributing factor that is commonly overlooked. Suami SIAGA is a campaign that has previously been enforced in Indonesia to promote paternal involvement pre- and post-birth with the hopes of instilling paternal responsibility and care for their partners for a better maternal outcome. Purpose – To analyse the effectiveness of the Suami SIAGA campaign in rural Indonesia as a campaign aiming to increase paternal involvement in community maternal healthcare Methodology – Literature search was conducted according to the PRISMA guidelines on international and national databases with additional materials from local university repositories until November 2020. A total of 600 studies were found with only cross-sectional studies being included. Critical appraisal of included studies was performed using the Newcastle-Ottawa Scale for quality assessment Findings – 4 peer reviewed cross-sectional studies were included in this review with a total of 55.139 couples intervened. The articles showed a positive association between the SIAGA status of husbands and improved participation in maternal healthcare especially in antenatal care visits, routine pregnancy checks and overall involvement in partners’ routines. Value– This review is the first in analysing the Suami SIAGA campaign and has valuable information in contributing to Sustainable Developmental Goals 3.7 on sexual and reproductive health